2007
DOI: 10.1177/001440290707300305
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Employment: Role of the Family in Career Development

Abstract: This study investigated the role of the family in career development and postschool employment outcomes for young adults with learning disabilities. Using a multiple-case study design, the authors examined a set of family structural and process variables. Fifty-nine in-depth interviews were conducted with young adults, parents, and school staff. Family structure was not directly linked to employment outcomes, but family socioeconomic status was related to initial career decision making and vocational identity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(99 citation statements)
references
References 27 publications
9
82
0
8
Order By: Relevance
“…In the introduction two models of family choice-making were presented (Snethen et al, 2006;Lindstrom et al, 2007). Although this study explored a variety of choices over a range of decisional areas (health, social care, education, leisure) and, particularly, focused on families with a child with learning disabilities, the concepts put forward by Snethen et al (2006) and The analysis presented here, however, extends this earlier work because it was possible to examine the roles parents assumed across different types of choicemaking situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the introduction two models of family choice-making were presented (Snethen et al, 2006;Lindstrom et al, 2007). Although this study explored a variety of choices over a range of decisional areas (health, social care, education, leisure) and, particularly, focused on families with a child with learning disabilities, the concepts put forward by Snethen et al (2006) and The analysis presented here, however, extends this earlier work because it was possible to examine the roles parents assumed across different types of choicemaking situations.…”
Section: Discussionmentioning
confidence: 99%
“…Two generic USA based studies offer models of the roles parents may assume and how, in consequence, this influences their child's involvement in choicemaking (Snethen et al, 2006;Lindstrom et al, 2007 To begin addressing gaps in the literature, this paper reports a study which, in part looked at parental perspectives on their and their child's role in choicemaking when there were significant choices to be made regarding their son/daughter's life. All the young people in this sample had learning disabilities.…”
Section: Choice-making In Familiesmentioning
confidence: 99%
“…In fact, research has indicated that when families are highly involved and advocate for the needs of their child during high school, those students with disabilities demonstrate better self-advocacy skills in secondary and postsecondary education settings (deFur, Todd-Allen, & Getzel, 2001;Morningstar et al, 1995;. In addition, secondary programs that encourage family and student involvement during transition planning have been associated with greater attainment of postschool outcomes such as employment, postsecondary education, community living, and community engagement (Devlieger & Trach, 1999;Lindstrom, Doren, Metheny, Johnson, & Zane, 2007). In fact, reported preliminary results from the NLTS-2 that high levels of parental involvement app eared to promote youth achievement.…”
Section: Quality Indicators Of Effective Secondary Transition Programsmentioning
confidence: 99%
“…En dicha toma de decisiones resulta esencial que los adolescentes sean capaces de desarrollar un proceso de exploración profesional, pensar sobre sus intereses ocupacionales, acceder a las fuentes de información correctas y reflexionar sobre el mundo del empleo (Turner y Lapan, 2002;Lozano y Repetto, 2007;Lindstrom et al, 2007;Noack et.al., 2010;Dietrich, Kracke y Nurmi, 2011;Santana, Vega y Santana, 2012). En definitiva, deberían ser competentes para llevar a cabo una "exploración para la carrera" entendida ésta como un conjunto de acciones deliberadas e intencionadas en las que ellos mismos como agentes que deben decidir, han de tomar un papel activo y que no se circunscribe únicamente al momento de la decisión final o definitiva.…”
Section: Introductionunclassified